The Legal Landscape of Patent for Innovative Startup Enterprises in Vietnam - Nhu Ha, Nguyen; Minh Phuong, Dang (VNU Journal of Science: Policy and Management Studies, 2025)
In the contemporary context, innovation is widely recognized as a pertinent strategy for achieving global and domestic sustainable development goals. The cultivation of a cohort of innovative startup enterprises has the potential to drive technological transitions, thereby aligning with both economic and sustainable development targets. However, innovative startup enterprises are encountering challenges within the intellectual property protection framework, particularly regarding patent protection – which should ideally serve as an effective safeguard for innovation. This study assesses the importance of patent protection laws for innovative startup enterprises in Vietnam, identifies deficiencies within the legal provisions, and proposes several recommendations for remediation.